A comparison of dichotomous IRT models based on continuous and discrete latent trait – Polish households’ saving skills - Genge, Ewa (Porównanie dychotomicznych modeli IRT o ciągłej i dyskretnej cesze ukrytej – umiejętność oszczędzania wśród polskich gospodarstw domowych, 2017)
Item response theory is considered to be one of the two trends in the methodological assessment of the reliability scale. Depending on the complexity of the adopted item parameterization, different types of IRT models for dichotomous items are defined. Most applications carried out in practice concern educational testing or psychological research and are based largely on the continuous assumption of the latent trait.The aim of this paper is to compare the estimation results of the discrete (formulated by the latent class approach) and continuous dichotomous IRT models in the analysis of Polish households’ saving skills as well as to assess Poles’ responses according to their ability to save money and the difficulty of the items (evaluation of the reliability of the item scale). All the computations and graphics in this paper are prepared using the MultiLCIRT and ltm packages of R
Ekonometria = Econometrics, 2017, Nr 3 (57), s. 37-46
Keywords: IRT theory; dichotomous IRT models; discrete and continuous latent trait; teoria IRT; dychotomiczne modele IRT; zmienna ukryta